Quantum computing without local control of qubit-qubit interactions. - Benjamin, S (2002)
If the interaction between qubits is not diagonal in the computational basis (e.g., the Heisenberg interaction), then one must be able to "switch it off" in order to prevent uncontrolled propagation of states. Therefore, schemes for quantum computing typically demand local control of the interaction strength between each pair of neighboring qubits. Here we demonstrate that this degree of control is not necessary: it suffices to switch the interaction collectively, something that can in principle be achieved by global fields rather than with local manipulations. This observation may offer a significant simplification for various implementations, including solid state and optical lattice schemes.